Chasing phantoms - Barton, Caitlin Rose (Rhodes University, 2026)
REVERIE is a screenplay that follows a young woman, Serene, in her late teens, who has a unique lucid dreaming ability. In SomniCity, a dystopian society, dreams are monitored and harvested to restore a broken, scorched world unbeknownst to its citizens. The city operates under the illusion of a feminist utopia with all men being exiled, and is sustained by surveillance, psychological control and experimentation. Serene’s role as dreamer gradually unravels as her reality starts to glitch—her dreams and memories folding into one another, exposing inconsistencies in and lies about her reality (like who her mother really is, whether she is an experiment, whether everyone is in on it). She is met by Silas, a young man trapped in The Wastes, who reaches her through her dreams. As Serene’s journey continues, she and Silas work hand-in-hand to unravel the secrets of her world. But with each of Serene’s dreams, SomniCity becomes increasingly unstable. Serene leaves her city on a quest to uncover The Wastes in hopes of finding her father—and some answers. Can she escape the control of SomniCity? Can she find the truth? By the epilogue, Serene is caught in a liminal space, between waking and dreaming, which leaves open the question whether she ever awakens or whether she remains trapped within the recursive dream system of SomniCity. REVERIE is about exploring dreams (both as narrative and form), testing boundaries and power, and discovering truth through memory and dreams. Chasing Phantoms: Harvesting Dreams as a Methodology for Radical Screenwriting (or Chasing Phantoms in short) began with dreams2 that refused to leave. Its images—a scorched world, an eerie meadow, a flood of ink, static of technology—haunted me long after waking. At the start of the research, I attempted to write the dream in order to understand its meaning and its pull. Soon I realised that what I was doing was not interpretation but a continuation—the dream that kept speaking. I realised that it was impossible to try and capture the dream content from start to finish and my recollection of these dreams proved unstable. Every time I woke up to recollect the dream, my mind was filled with gaps—secrets that the dream locked away from my conscious mind. However, the feeling of the dream lingered and unsettled me as I struggled to recall it. This feeling of unstable recollection led me to my research inquiry: How do dreams function? How can dreams serve both as a source and method of screenwriting, using the act of writing itself as a form of discovery? Today, this project questions how dream-writing functions through form and structure—how it loops, ruptures, fragments, repeats. It asks how dream logic might be translated into a screenwriting practice to expand what a screenplay can hold and how it can think and breathe. The objective of this research was to develop an alternative, radical approach to screenwriting practice through its methodology; a methodology that resists linearity and the hierarchies of traditional narrative form. Perhaps this was a very ambitious task, as REVERIE still holds traces of the rational, linear narrative to follow Serene’s journey—but the essence lies in the way it is subtly challenged. While REVERIE follows the three-act structure, the screenplay subverts it through dreambleeds that override narrative logic, fragmentation, temporal speech and action (fast and slow-paced) that disrupt predictable rhythms, and textual or typographic patterns that destabilise language and order. These subtle interventions maintain coherence for the viewer while constantly unsettling narrative expectations. This methodology aims to open the process of writing to intuition, sensation, experience and embodied knowledge. I sought to write with the dream rather than about the dream. To let the subconscious (that which exists in the mind but is not immediately available to the conscious, waking mind—the dream) guide the structure, imagery, and rhythm of the screenplay. To me, that is the key focus of REVERIE—exploring the entirety of dream-writing and what it means, how it functions, and what it can achieve. Chasing Phantoms draws on Hélène Cixous’s concept of l’écriture féminine and her notion of jouissance, which are methods of writing through the body as a means of resistance, experience and emotion. The project also utilises Hans-Thies Lehmann’s theory of postdramatic temporality, specifically his concept of durational aesthetics, which reimagines time as cyclical and durational rather than linear—tying it together with dream temporality. Furthermore, arts-based research perspectives from Laurel Richardson and Elizabeth St. Pierre particularly embodied writing, and writing as a method of inquiry, inform the research inquiry and the process of discovery through writing. Together, these ideas lay the groundwork on which I built my approach to treating dreams not as metaphors, but as a method—an epistemology of fluidity, disorientation and constant return. The result of this methodology birthed REVERIE.
harvesting dreams as a methodology for radical screenwriting
Keywords: Creative writing (http://id.loc.gov/authorities/subjects/sh85033847); Dreams and the arts (http://id.loc.gov/authorities/subjects/sh2003001414); Feminist films (http://id.loc.gov/authorities/subjects/sh85047754); Femininity in literature (http://id.loc.gov/authorities/subjects/sh94004221); Drama; Embodied writing (https://www.wikidata.org/wiki/Q55647773); Screenwriting (https://www.wikidata.org/wiki/Q3429919); Practice research (https://www.wikidata.org/wiki/Q7237362)